2004
DOI: 10.1063/1.1633344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen related defects on the electrical and thermal behavior of a n+−p junction

Abstract: This study examines the electrical and temperature behavior of two of the levels in Czochralski-grown silicon that are most detected by different authors. A comparison between an analytical expression of the generation recombination noise in pϪn junctions with experimental data taken from other authors was used as a tool for determining capture cross sections and densities of oxygen related traps in silicon. The parameters found in the literature for a deep level located at E C Ϫ0.43 eV are verified in this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Kot et al [ 9 ] investigated the evolution of the electron states in n‐Cz‐Si samples with an increase of the annealing temperature and found an additional shallow level E c − 0.16 eV that was attributed to rod‐like defects accompanied by OPs growth process. Such an OP‐related level was also reported by Tejada et al [ 10 ]…”
Section: Introductionsupporting
confidence: 83%
“…Kot et al [ 9 ] investigated the evolution of the electron states in n‐Cz‐Si samples with an increase of the annealing temperature and found an additional shallow level E c − 0.16 eV that was attributed to rod‐like defects accompanied by OPs growth process. Such an OP‐related level was also reported by Tejada et al [ 10 ]…”
Section: Introductionsupporting
confidence: 83%
“…Thus, the pn-junction leakage current increased. Jimenez et al, demonstrated that the oxygen-related-deep-level defects such as oxygen precipitates affect the pn-junction leakage current after the device heat treatment (41). In contrast, Figure 7(b) indicates that the pn-junction leakage current of the hydrocarbon molecular-ion-implantation is lower with SAB than without SAB.…”
Section: Ecs Transactions 86 (5) 77-93 (2018)mentioning
confidence: 95%
“…Although its contribution to the low frequency noise is negligible, the reason to study this trap is to analyze its effect on the conducting channel of the device, one of the objectives of this work. The presence of these two bulk levels may be associated with different forms of oxygen precipitates [12][13][14].…”
Section: Evolution Of the Drain-current Noise With The Junction-gate mentioning
confidence: 99%